Dermal papilla cells-conditioned medium attenuates oxidative stress-induced senescence via ferroptosis inhibition - Zha Ru; Yu Wu; Qian Qu; Yong Miao; Lei Zhu; Zhiqi Hu (Scientific Reports)
Abstract Skin photoaging results primarily from chronic ultraviolet (UV) exposure, which disrupts dermal homeostasis and promotes cellular senescence. Dermal papilla cell-conditioned medium (DPC-CM) has emerged as a promising cell-free approach for skin rejuvenation. This study aimed to explore the anti-photoaging effects of DPC-CM and its potential regulation of ferroptosis. Mouse dermal papilla cells and skin fibroblasts were isolated and characterized. A photoaging model was established using UVA-irradiated fibroblasts, followed by treatment with DPC-CM at two concentrations, the ferroptosis inhibitor ferrostatin-1 (FER-1), or retinoic acid. UVA exposure led to reduced cell viability, impaired migration, increased senescence, elevated iron and reactive oxygen species levels, decreased glutathione, and altered expression of ferroptosis-related markers including nuclear factor erythroid 2-related factor 2 (NRF2), glutathione peroxidase 4 (GPX4), and solute carrier family 7 member 11 (SLC7A11). These changes were partially reversed by DPC-CM and FER-1. Proteomic analysis revealed that proteins in both dermal papilla cells and DPC-CM are associated with ferroptosis pathways. In vivo, DPC-CM significantly attenuated UVA-induced dermal aging. Collectively, these findings demonstrate that DPC-CM protects against photoaging by modulating ferroptosis, supporting its therapeutic potential in oxidative stress-related skin disorders.